Review of Crosslinguistic influence and second language learning by Kevin McManus - Zhu, Lixia; Cai, Jinting (Studies in Second Language Learning and Teaching, 2022)
As a prevalent phenomenon in second language acquisition (SLA), crosslinguistic influence (CLI) has attracted ever-lasting attention, as reflected by the publication of several monographs (e.g., Cai, 2021; Jarvis & Pavlenko, 2008; Odlin, 1989; Ringbom, 2007), many edited volumes (e.g., Alonso, 2016; Gass & Selinker, 1983), and numerous research articles. In these books and papers, mounting evidence for CLI has been accumulated in various areas of languages. In particular, CLI may occur between first language (L1) and second language (L2) in lexicon, grammar, phonology, discourse, and pragmatics, with its effects being both positive and negative. Besides, it has been shown that the occurrence of CLI is constrained by a variety of factors, such as linguistic and psycholinguistic factors and those related to learning environment and language use (Jarvis & Pavlenko, 2008). CLI has been addressed from diverse theoretical perspectives including universal grammar, functional linguistics, and psycholinguistics (see Cai, 2021 for a review).